2015
DOI: 10.1111/evj.12446
|View full text |Cite
|
Sign up to set email alerts
|

Head and pelvic movement asymmetry during lungeing in horses with symmetrical movement on the straight

Abstract: SummaryReasons for performing studyLungeing is commonly used as part of standard lameness examinations in horses. Knowledge of how lungeing influences motion symmetry in sound horses is needed.ObjectivesThe aim of this study was to objectively evaluate the symmetry of vertical head and pelvic motion during lungeing in a large number of horses with symmetric motion during straight line evaluation.Study designCross‐sectional prospective study.MethodsA pool of 201 riding horses, all functioning well and considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 26 publications
12
97
0
Order By: Relevance
“…The horse-rider´s interaction has also been studied and the graphics of rider movement have been consistent with those reported by the horse trunk (Halling-Thomsen et al 2010, Eckardt et al 2014, Rhodin et al 2016. Following this line, Miro et al (2006) conducted a comparison of the horse's gait with and without riders, where they found no difference between the two movement conditions.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…The horse-rider´s interaction has also been studied and the graphics of rider movement have been consistent with those reported by the horse trunk (Halling-Thomsen et al 2010, Eckardt et al 2014, Rhodin et al 2016. Following this line, Miro et al (2006) conducted a comparison of the horse's gait with and without riders, where they found no difference between the two movement conditions.…”
Section: Introductionmentioning
confidence: 61%
“…The development of photogrammetry and accelerometry have enabled a more detailed study of motion (Keegan et al 2004, Abson et al 2015. The studies have focused primarily on the analysis of the gait symmetry of horses to identify potential injury (Rhodin et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ; Rhodin et al . , ). The comparatively high percentage (up to 67%) of Polo horses found outside previously reported clinical thresholds (Pfau et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in over 90 horses found to present within stringent symmetry thresholds on the straight, showed a more mixed distribution between increased head drop during inside and outside forelimb stance (Rhodin et al . ). It seems noteworthy that in these horses the head asymmetry is generally of a small magnitude with mean values of 6–9 mm in both lungeing directions.…”
Section: Quantifying Clinically Relevant Exercisementioning
confidence: 97%